2000
DOI: 10.1002/1099-1727(200022)16:2<113::aid-sdr189>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Using system dynamics to analyse interactions in duopoly competition

Abstract: This article introduces non‐linear dynamics to assess the interactions in duopoly competition between two rivals. The generic competition is considered here to be the competition for quality between two consumer durable products. The authors have used a system dynamics approach to develop the model of interactions and simulate the behaviour over time. The outcomes of several hundred simulations have shown that the recognition and implementation lags in quality improvement strongly influence the qualitative beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Kim and Kim (1997) proposed an SD model for a mixed-strategy game between police and driver and carried out a qualitative analysis on its simulation result. Sice, Mosekilde, Moscardini, Lawler, and French (2000) used an SD approach to develop the model of interactions in duopoly competition between two rivals and simulated the behaviour over time, which showed that the model exhibited complex counter-intuitive behaviours instead of tending to equilibrium around an optimal value. SD will simulate evolutionary processes of games towards (non-)equilibrium states, while game theory provides framework for modelling the world, which is full of both competition and cooperation with all kinds of uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…Kim and Kim (1997) proposed an SD model for a mixed-strategy game between police and driver and carried out a qualitative analysis on its simulation result. Sice, Mosekilde, Moscardini, Lawler, and French (2000) used an SD approach to develop the model of interactions in duopoly competition between two rivals and simulated the behaviour over time, which showed that the model exhibited complex counter-intuitive behaviours instead of tending to equilibrium around an optimal value. SD will simulate evolutionary processes of games towards (non-)equilibrium states, while game theory provides framework for modelling the world, which is full of both competition and cooperation with all kinds of uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…It is easy to see that condition (22) will be satisfied if c 11 = c 22 , c 12 = c 21 , k 11 = k 22 . Section V-D will show that (22) predicts the location of the sliding equilibrium exactly, when c 12 is varied (but all equalities are maintained).…”
Section: B Analysis Of Modelmentioning
confidence: 99%
“…Section V-D will show that (22) predicts the location of the sliding equilibrium exactly, when c 12 is varied (but all equalities are maintained).…”
Section: B Analysis Of Modelmentioning
confidence: 99%
See 2 more Smart Citations